2000
DOI: 10.1002/jccs.200000097
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bacteriochlorophyll Anion Band at 1020 nm Produced by Nuclear Wavepacket Motion in Bacterial Reaction Centers

Abstract: Formation of a nuclear wavepacket on the potential energy surface of the primary electron donor P" induced by 30-fs excitation ofpheophytin-modifiedRhodobacter sphaeroides R-26 reaction centers leads to a reversible and irreversible appearance of the state P+B A ' monitored by the measurements of the 1020-nm band which is characteristic of the radical anion band of bacteriochlorophyll monomer B A ' . The reversible appearance of the state P+B A ' is characterized by two (130 and 320 em") vibration modes and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 32 publications
6
32
0
Order By: Relevance
“…To study these possibilities, femtosecond (fs) coherent spectroscopy and the frequency analysis of vibration and rotation of the molecular groups involved in charge separation have recently been applied. [21][22][23][24][25][26][27][28][29] This approach in combination with site-directed mutagenesis of the RC protein offers an opportunity to address the problem of stabilization of separated charges as well.…”
Section: Introductionmentioning
confidence: 99%
“…To study these possibilities, femtosecond (fs) coherent spectroscopy and the frequency analysis of vibration and rotation of the molecular groups involved in charge separation have recently been applied. [21][22][23][24][25][26][27][28][29] This approach in combination with site-directed mutagenesis of the RC protein offers an opportunity to address the problem of stabilization of separated charges as well.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in RCs the wave packet is initially formed by femtosecond light pulses on the 130-140 cm -1 potential energy hypersurface of P*. The subsequent motion on this surface leads the wave packet to the intersection region between P* and P + B Alocated close to the long-wavelength side (935 nm) of the stimulated emission band of P* (3,(31)(32)(33)(34). At 120 fs and mostly at 380 fs delays the wave packet reflects from the P* surface wall and is not stabilized onto the P + B Asurface at room temperature.…”
mentioning
confidence: 99%
“…sphaeroides R-26 RCs by measuring oscillations in the kinetics of the absorbance increase at 1,020 nm that is characteristic for B − A radical anion formation. 5,24,[68][69][70][71] The oscillating motions of the wave packet on the P * potential energy surface towards the long-wavelengthstimulated emission region (935 nm) were shown to be accompanied by a reversible electron transfer from P * to B A . This results in modulated formation of the 1,020-nm absorption band of B − A with the initial period of about 260 fs.…”
Section: Introductionmentioning
confidence: 95%
“…63,64 Coherent components have also been observed in the kinetics of population of the product charge-separated states, P + B − A and P + H − A . [67][68][69][70][71][72] Modulation of the population of the P + B − A state has been detected in Rb. sphaeroides R-26 RCs by measuring oscillations in the kinetics of the absorbance increase at 1,020 nm that is characteristic for B − A radical anion formation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation